2020
DOI: 10.1097/cmr.0000000000000690
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistiocytosis in advanced melanoma treated with dabrafenib and trametinib combination: two cases

Abstract: Hemophagocytic lymphohistiocytosis (HLH) has been only rarely reported in patients with BRAF-mutated advanced melanoma treated with targeted therapies and never with first-line dabrafenib/trametinib combination thus far. Two patients treated with first-line dabrafenib and trametinib combination therapy for metastatic melanoma presented with sudden occurrence of fever, cytopenia, rhabdomyolysis, hepatic cytolysis, hypertriglyceridemia and very high ferritin levels after few weeks of treatment, associated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…4 In literature, few cases have described MAS during progressive tumour with dabrafenib and trametinib used for metastatic melanoma. 5,6 In one of those case reports, 6 patient also developed MAS 5 months after the initiation of dabrafenib trametinib (8 months in our case) which was disappeared after discontinuation of treatment. In our case, MAS appeared during adjuvant therapy without signs of progressive tumour.…”
Section: Macrophage Activation Syndrome Associated With Braf and Mek ...supporting
confidence: 54%
“…4 In literature, few cases have described MAS during progressive tumour with dabrafenib and trametinib used for metastatic melanoma. 5,6 In one of those case reports, 6 patient also developed MAS 5 months after the initiation of dabrafenib trametinib (8 months in our case) which was disappeared after discontinuation of treatment. In our case, MAS appeared during adjuvant therapy without signs of progressive tumour.…”
Section: Macrophage Activation Syndrome Associated With Braf and Mek ...supporting
confidence: 54%
“…In some cases, the authors suggested that a change in targeted therapies was sufficient to control the evolution of HLH [4]. In our situation, the patient relapsed a second time, which motivated us to start corticosteroid therapy at 0.5 mg/kg/day while maintaining actual DTT to achieve a therapeutic response, as reported in two cases [5].…”
mentioning
confidence: 73%
“…Less than 40 cases of HLH during dabrafenib/trametinib therapy have been reported in the literature [3,4] and international pharmacovigilance database (VigiLyze), and only four cases have been reported during vemurafenib/cobimetinib therapy, which is mostly prescribed for first-line melanoma treatment. The median time lag between the initiation of DDT and the development of HLH was 33 days (6 days–6 months) when data were available.…”
mentioning
confidence: 99%
“…In the literature there are available case reports in which treatment interruption or corticosteroids alone were used with sufficient response (Sadaat and Jang, 2018;Mizuta et al, 2020;Gambichler et al, 2021). In melanoma patients HLH can be also attributed to a solid tumour as a first presentation of the disease (Stabler et al, 2017), Epstein-Barr virus (EBV) infection (Davis et al, 2019) and can be associated with BRAF/MEK inhibitors (Samaran et al, 2020;Dudda et al, 2021). These cases represented rather moderate HLH where treatment discontinuation, basic supportive care (intravenous rehydration and paracetamol), and low dose steroids (or even without steroids prescription) (Samaran et al, 2020) were sufficient methods of treatment.…”
Section: )mentioning
confidence: 99%
“…In melanoma patients HLH can be also attributed to a solid tumour as a first presentation of the disease (Stabler et al, 2017), Epstein-Barr virus (EBV) infection (Davis et al, 2019) and can be associated with BRAF/MEK inhibitors (Samaran et al, 2020;Dudda et al, 2021). These cases represented rather moderate HLH where treatment discontinuation, basic supportive care (intravenous rehydration and paracetamol), and low dose steroids (or even without steroids prescription) (Samaran et al, 2020) were sufficient methods of treatment. In 19% of cases in VigiBase, concomitant Epstein-Barr virus infection was reported, suggesting a potentially augmented immune response in case of chronic underlying infection (Davis et al, 2019).…”
Section: )mentioning
confidence: 99%